Carbon Dioxide Captured on a Wet Si−C Composite Material with a Surfactant‐derived Carbon Film. Issue 19 (18th May 2022) - Liu, Xiuwu; Zhu, Shijie; Chen, Xueqing; Cui, Xiaoyuan; Cao, Jilin
Abstract: The storage capacity of carbon dioxide (CO2 ) on the wet SBA‐15 material can be greatly improved by forming gas hydrates. The presence of generous polar groups (hydroxyl groups) on the surface of SBA‐15 hinders the formation of CO2 hydrates. In order to further improve its CO2 adsorption capacity, the polar surfaces of SBA‐15 material are changed into non‐polar carbon surfaces by covering with carbon film, and Si−C composite is obtained. Compared with the SBA‐15 material, the pore size and pore volume of the Si−C composite material reduces but its morphology and structure are unchanged. Whether pre‐adsorbed water or not, the experiment results showed that the Si−C composite material is more conducive to the adsorption of CO2 than the SBA‐15 material. In a comparison of the Si−C composite material and the SBA‐15 material at 2.5 MPa, the CO2 adsorption capacity increased from 3.8 mmol/g to 8.5 mmol/g with dry samples, and the CO2 adsorption capacity increased from 20.1 mmol/g to 26.9 mmol/g with wet samples at Rw =2.0. Abstract : The polar surfaces of SBA‐15 material are changed into non‐polar carbon surfaces by covering with carbon film, and Si−C composite is obtained. In a comparison of the Si−C composite material and the SBA‐15 material at 2.5 MPa, the CO2 adsorption capacity increased from 3.8 mmol/g to 8.5 mmol/g with dry samples, and the CO2 adsorption capacity increased from 20.1 mmol/g to 26.9 mmol/g with wet samples at Rw =2.0.